Yeast-derived low-purity FGF2 supports bovine ESC and MSC aggregates in suspension - Savyon, Gaya; Tawil, Shadi; Tadmor, Yuval; Shimshi, Atar; Porat, Yair; Agmon, Neta; Schlesinger, Sharon; Tuller, Tamir; Nachman, Iftach (Frontiers in Nutrition, 2025)
Fibroblast Growth Factor 2 (FGF2) is an essential component of media for cultivated meat production, supporting the proliferation, survival, and differentiation of various cell types. The high cost of recombinant FGF2, typically produced in Escherichia coli (E. coli) with laborious downstream processing, remains a major bottleneck to commercial scalability. In this study, we developed a low-cost production platform using Pichia pastoris (P. pastoris), a food-grade yeast capable of secreting properly folded proteins into the culture medium. We produced bovine FGF2 and purified it using tangential flow filtration (TFF), omitting chromatography to reduce processing complexity and cost. The biological activity of these low-purity FGF2 variants was assessed in two relevant models: bovine embryonic stem cells (bESCs) cultured as 3D aggregates under fully defined, animal component-free conditions, and immortalized bovine mesenchymal stem cells (bMSCs) in both 2D and 3D formats. Across all assays, the yeast-derived FGF2 variants matched or exceeded the performance of commercial high-purity FGF2 in promoting aggregate growth, mesodermal differentiation, and cell proliferation. Notably, both liquid and freeze-dried formulations of the TFF-purified FGF2 showed robust functionality, underscoring their suitability for industrial applications. These findings demonstrate that simplified, chromatography-free production of bioactive FGF2 is feasible and effective, offering a scalable and economically viable solution for next-generation cultivated meat media.